Pengembangan Lembar Kerja Siswa Berbasis STEAM untuk Siswa Sekolah Dasar - Haifaturrahmah Haifaturrahmah; Romi Hidayatullah; Sri Maryani; Nurmiwati Nurmiwati; Azizah Azizah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
The aim of this research is to develop and evaluate STEAM based student worksheet book (LKS). This research used Research Design, development ADDIE’s Model consisting of Analysis, Design, Development, Implementation and Evaluation. This research had been implemented in SDN 05 Aikmel, in which the population of the study was 23 students of the third grade. It had 6 samples where the samples were taken by purpose sampling method with low, medium, and high achievement criteria. The collected data were gained by interview and questionnaire. The gained data were then analyzed by using rating scale, on a scale of 5 which were subsequently converted to qualitative data. The result of the study showed that the average value of the experts was 4, 28 with very good category, while the user response (teachers and students) was 4, 55 with a very good category. The conclusions of this research shows that STEAM based student worksheet book which is developed eligibel and can be used as a supporting learning resources for 2013 curriculum based thematic learning.